2017
DOI: 10.4172/2375-446x.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use Efficiency and Invasive Potential of Non-Native Fish Species, Oreochromis niloticus from the Paisuni River, India

Abstract: Oreochromis niloticus species are adapted to their own set of local ecological and climatic conditions from the Paisuni river, India. Consequently, environmental conditions and their connectivity to organisms may play a big role in generating growth outcome of non-native species in natural conditions. Study was undertaken during the period of October 2015 to September 2016 from the Paisuni river, India. Invasive potential of O. niloticus was measured through size composition, age and growth from the Paisuni ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[42] Dwivedi and Mayank (2013) reported that the C. carpio attained an average length of 19.0, 26.7, 37.5, 41.1, 45.5, 49.6, 54.9, 59.5, 63.1, 66.2, 70.9 and 76.2 cm, respectively at the end of 1+ to 12+ years of the life cycle from the Yamuna River, Uttar Pradesh, India. Several factors can account for the fluctuation in the age and growth rate as like quantity and quality of available food, the richness of species, density of exotic species (Example especially Cyprinus carpio) quality of the water (For example organic load, heavy metal concentration), maturity and spawning cycle [57][58][59][60][61][62][63][64][65][66][67][68][69]. This species can typically live for around 20 years in the wild freshwater ecosystem (for example rivers) [70][71].…”
Section: Resultsmentioning
confidence: 99%
“…[42] Dwivedi and Mayank (2013) reported that the C. carpio attained an average length of 19.0, 26.7, 37.5, 41.1, 45.5, 49.6, 54.9, 59.5, 63.1, 66.2, 70.9 and 76.2 cm, respectively at the end of 1+ to 12+ years of the life cycle from the Yamuna River, Uttar Pradesh, India. Several factors can account for the fluctuation in the age and growth rate as like quantity and quality of available food, the richness of species, density of exotic species (Example especially Cyprinus carpio) quality of the water (For example organic load, heavy metal concentration), maturity and spawning cycle [57][58][59][60][61][62][63][64][65][66][67][68][69]. This species can typically live for around 20 years in the wild freshwater ecosystem (for example rivers) [70][71].…”
Section: Resultsmentioning
confidence: 99%
“…In general, C. carpio and O. niloticus have not any ecological standard from the lotic ecosystem [5,[43][44][45].Both species are commercially exploited from the Ganga basin [46] and highly utilize natural resources, threat biodiversity of fishes and damage indigenous fish stock [47][48][49]. But reproductive system and recruitment process are damaging by high concentration of metals in fish body [50][51][52][53].…”
Section: Chemical Oxygen Demand (Cod)mentioning
confidence: 99%
“…Freshwater ecosystems touch nearly all aspects of human society [12]. Fishing, anthropogenic and invasive species are among the most important stressors which are affecting freshwaters fish stock from the lotic and lentic ecosystem (e.g.…”
Section: Introductionmentioning
confidence: 99%